Dynamic mode II delamination in through thickness reinforced composites - Yasaee, M; Mohamed, G; Pellegrino, A; Petrinic, N; Hallett, SR (Springer, Cham, 2016)
Through thickness reinforcement (TTR) technologies have been shown to provide effective delamination resistance for laminated composite materials. The addition of this reinforcement allows for the design of highly damage tolerant composite structures, specifically when subjected to impact events. The aim of this investigation was to understand the delamination resistance of Z-pinned composites when subjected to increasing strain rates. Z-pinned laminated composites were manufactured and tested using three point end notched flexure (3ENF) specimens subjected to increasing loading rates from quasi-static (~0 m/s) to high velocity impact (5 m/s), using a range of test equipment including drop weight impact tower and a split Hopkinson bar (SHPB). Using a high speed impact camera and frame by frame pixel tracking of the strain rates, delamination velocities as well as the apparent fracture toughness of the Z-pinned laminates were measured and analysed. Experimental results indicate that there is a transition in the failure morphology of the Z-pinned laminates from quasi-static to high strain rates. The fundamental physical mechanisms that generate this transition are discussed.